Duration of Exclusive Breastfeeding, Housing and Environmental Conditions as Risk Factors of Pneumonia among Under–Five Children at Public Health Center II South Denpasar - Ni Kadek Ethi Yudiastuti; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Universitas Udayana, 2015)
Background and purpose: In 2012, the South Denpasar II Public Health Center (PHC) had the 2nd highest percentage of reported cases of pneumonia (15.9%). This study aims to determine duration of exclusive breastfeeding, housing and environment conditions as risk factors of pneumonia among under-five children. Methods: The study design was a case control. The cases were 60 under-five children with pneumonia and recorded in the PHC register between 1 January 2014 to 31 March 2015. Controls were 60 healthy under-five children visiting the PHC during study. Interviews with parents were conducted using questionnaires, and observation carried out using specific guidelines. Measurements of house physical environment variables were conducted using hygrometer, lux meter and roll meter. Data were analyzed using Stata SE 12.1. Results: Characteristics of mothers were comparable in terms of age, education, and income; while the children were comparable in terms of age and gender. Risk factors found to increase pneumonia were duration of exclusive breastfeeding <2 months with OR=5.24 (95%CI: 1.96-14.01), no Hib and pneumococcal immunization with OR=3.68 (95%CI: 1.11-12.17), access to natural lighting with OR=2.72 (95%CI: 1.05-7.00) and house density with OR=3.11 (95%CI: 1.18-8.19). Frequency of acute respiratory tract infection (ARTI) >1 time in 6 months with OR=10.14 (95%CI: 3.67-28.02) were also found to be risk factors. Conclusion: Duration of exclusive breastfeeding, lack of natural lighting and house density were risk factors for pneumonia among under-five children.